The birds of the lake of Pinarbasi, Malatya - Ayvaz, Y. (My University, 1990)
Reviews the avifauna following use of the lake as a picnic area. -from English summary
Malatya Pinarbasi golu kuslari
Keywords: Malatya; Pinarbasi; Turkey; avifauna; bird